Hospitality Education In Allahabad –A Student’s Perspective (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: This paper emphasizes on significance of hospitality education keeping in view the  student’s perspective in the city of Allahabad. Hospitality education opens a wide range of career  prospects related to hotel and tourism management, restaurant management, culinary art, retail  and financial management. Objective: To assess the student’s perspective regarding Hospital ity education. Method: The data was collected by the means of questionnaire from 100 students  of class 12th of various streams studying at different coaching centres of Allahabad. Result: The  subjects had strong awareness regarding hospitality industry, out of which 84% believed it as an  excellent career option. All the Commerce students believed that Hospitality management is a viable career option for them whereas only 75% of the Science and Arts students believed so. All the  Science and Commerce students believed that there is no favourable atmosphere and career pros pects for Hospitality Management graduates in the city of Allahabad whereas only 67% of the Art  students share the same opinion. Conclusion: There is a need for state and central governments to  focus on the tourism development of the city which has a lot of potential.
Keywords: Hospitality Education; Science; Commerce; Arts; Allahabad